The Polyglutamine Expansion in Spinocerebellar Ataxia Type 6 Causes a β Subunit-Specific Enhanced Activation of P/Q-Type Calcium Channels in Xenopus Oocytes - Restituito, Sophie (J Neurosci, 2000)
Spinocerebellar ataxia type 6 (SCA6) is a dominantly inherited degenerative disorder of the cerebellum characterized by nearly selective and progressive death of Purkinje cells. The underlying mutation in SCA6 consists of an expansion of a trinucleotide CAG repeat in the 3′ region of the gene, CACNA1A, encoding the α(1A)subunit of the neuronal P/Q-type voltage-gated calcium channel. Although it is known that this mutation results in an expanded tract of glutamine residues in some α(1A) splice forms, the distribution of these splice forms and the role of this mutation in the highly selective Purkinje cell degeneration seen in SCA6 have yet to be elucidated. Using specific antisera we demonstrate that the pathological expansion in SCA6 can potentially be expressed in multiple isoforms of the α(1A) subunit, and that these isoforms are abundantly expressed in the cerebellum, particularly in the Purkinje cell bodies and dendrites. Using α(1A) subunit chimeras expressing SCA6 mutations, we show that the SCA6 polyglutamine expansion shifts the voltage dependence of channel activation and rate of inactivation only when expressed with β(4)subunits and impairs normal G-protein regulation of P/Q channels. These findings suggest the possibility that SCA6 is a channelopathy, and that the underlying mutation in SCA6 causes Purkinje cell degeneration through excessive entry of calcium ions.